On the electronic structure and photochemistry of coordinatively unsaturated complexes: the case of Nickel bis-dinitrogen, Ni(N2)2 - Hübner, Olaf; Manceron, Laurent; Himmel, Hans-Jörg (Chemistry - a European journal, 2014)
The electronic ground and excited states of the coordinatively unsaturated complex Ni(η1-N2)2, isolated in an Ar matrix, are analyzed in detail by vibrational and electronic absorption and emission spectroscopies allied with quantum chemical calculations. The bond force constants are determined from a normal coordinate analysis and compared with those of the isoelectronic carbonyl complex. The consequences for the bond properties are discussed, and the trend in the force constants is compared with the standard formation enthalpies. The linear complex Ni(η1-N2)2 with two terminal dinitrogen ligands can be photoisomerized to two isomeric, metastable forms Ni(η1-N2)(η2-N2) and Ni(η2-N2)2, with one and two side-on coordinated dinitrogen ligands, respectively.
Die Zahl 2 ist im Zusatz zum Titel tiefgestellt
Gesehen am 21.10.2020